Patterns of serologic markers of hepatitis B virus infection and the risk of transmission among pregnant women in southwestern Nigeria (2017)
Hepatitis B virus (HBV) infection is a major health concern in developing countries that has a high morbidity and mortality rate. Vertical transmission of HBV from mother to child has been identified as a major factor leading to chronicity with attendant liver conditions, especially in poor socioeconomic settings. This study aims to evaluate the prevalence of serological HBV markers among pregnant women in Ibadan southwestern Nigeria and to determine the implications for perinatal HBV transmission. This study revealed the presence of varied HBV serological patterns of infection or immunity among pregnant women in Ibadan, Nigeria, and thus the risk of mother to child transmission.